DRUG AFFORDABILITY IN INDIA - POST 2005 - RUCHIKA NANDHA (International Journal of Pharma and Bio Sciences, 2013)
Indian pharmaceutical industry so far has reformed globally as a powerhouse for production of drugs after implementation of Indian patent act (IPA) in 1970. After implementation of Trade Related Aspects of Intellectual Property Rights (TRIPS) act on March 23, 2005, India’s weak process patent system has been replaced by a strict product patent system resulting in a big question mark on the affordability of medicines. Judicious use of inbuilt flexibilities available in the TRIPS, introduction of utility models and industrial design patents, medical insurance to all, elimination of heavy duties and taxes on medicines and regulation of markups, promotion of generic medicines, improved availability of medicines in the public sector , transparency in the supply chain are the key strategies needed to be implemented and regulated at national level to secure the peoples’ rights of access to affordable and quality health care.